Acute limb ischemia with concomitant splenic and renal infarcts: Thromboembolic events revealing COVID-19 - Berrichi, Samia (Ann Med Surg (Lond), 2021)
INTRODUCTION: Since December 2019, the coronavirus 19 (COVID-19) pandemic continues to spread worldwide and has caused millions of deaths. Although the main manifestation of the disease is acute respiratory distress syndrome, hypercoagulability resulting from hypoxemia leads to venous thromboembolism and arterial thrombosis, which have a fatal prognosis for COVID-19. CASE REPORT MANAGEMENT: We report the case of patient admitted to our unit for management of a concomitant limb ischemia, splenic and renal infarcts associated to a COVID-19 infection with favorable outcomes after thrombectomy and therapeutic doses of heparin. CONCLUSION: Systemic procoagulant manifestations related to a COVID-19 infection is a newly described phenomenon responsible of cardiovascular and neurological disorders.